Room Temperature, Metal-Free, Radical Chloroazidation of 1,6-Enynes - Ying, Wei-Wei; Chen, Wei-Ting; Bao, Wen-Hui; Gao, Le-Han; Wang, Xin-Ye; Chen, Gan-Ping; Ge, Guo-Ping; Wei, Wen-Ting (Synlett, 2018)
Without employing any transition metal, a mild, practical, and environmentally attractive methodology has been developed for the chloroazidation of 1,6-enynes at room temperature. In this radical cascade process, three new chemical bonds, including C–Cl (Br, I), C–N, and C–C bonds, are formed in one step for the construction of 2-pyrrolidinones. The method is valuable because of its mild reaction conditions, operational simplicity, and the rich biological activity of the corresponding 2-pyrrolidinone products.
Keywords: room-temperature reactions; metal-free reactions; radicals; cascade processes